Defining the rural area in Romania: Legislative approaches - Violeta Stanciu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
This article is an analysis of how the rural area was defined in the Romanian legislation starting with the oldest law in force until last legislative initiatives in the field. The texts of Romanian legal acts were studied comparatively and against the provisions of the European Charter of Rural Areas. It was found that the definition of rural area in Romania was done generally by comparison and even in opposition to urban area. The new European paradigm emphasizes the complementarity of the two areas, different as specificity but equally important. Thus, the European Union's aim is no longer to transform rural into urban but to preserve and capitalize the specificity of each area in order to increase the living standards of all citizens, to maintain a healthy natural environment and to comply with the principles of sustainable development. National legislation does not seem to keep up with these trends, the biggest risk identified so far being a low rate of absorption of European funds. To avoid blockages, the documents providing the access to finance found, however, solutions for choosing beneficiaries specific to them. However, redefining the Romanian rural area within the national legislation, rigorously and in compliance with current European trends is a necessity for the elaboration of sustainable development policies in the medium and long term.
Keywords: P25; A12; D63; 330; rural environment; urban environment; territorial administration; rural development; urbanization indicators